Factors that cause compliance filling medical records in hospitals - Rahmatiqa, Chamy; Abdillah, Nurul; Yuniko, Fajrilhuda (International Journal Of Community Medicine And Public Health, 2020)
Hospital recording system guidelines or known as medical records. Failure to fill medical records has an impact on the quality of service and hospital accreditation. The purpose of this study is to see what factors are the cause of non-compliance in filling Medical Records in hospitals throughout Indonesia. Research is a systematic review. The source of this research data comes from the literature obtained through the internet in the form of published research results regarding the causes of the inability of medical record documents in hospitals from all journals that have been published and can be accessed via the internet. Data was collected from 15 April 2020-10 July 2020. The results of the analysis through document review showed that the factors causing non-compliance of filling medical record documents at the High Hospital were human resources which were 66.6%, there was no clear and firm policy of 33.3%, facilities that did not support were 22.2% and limited funds by 11.1%. It is expected that each hospital must have a clear and firm policy in dealing with non-compliance with filling out this medical record document. With a clear and firm policy on the condition of HR unpreparedness, the facilities and financial conditions which will also be regulated in the policy can also be overcome at the same time.